LITERASI ULAMA DAN WACANA KEISLAMAN AWAL ABAD KE-20 DI SULAWESI SELATAN - Abd Kadir Ahmad (Al-Qalam, 2019)
This paper aims to (1) explore the writings of ulama especially in the early 20th century in South Sulawesi, (2) identify the religious discourse that developed at the time, and (3) encourage the preservation of the spirit of literacy for present and future scholars. This writing is a literature study on the writing of Haji Ahmad Bone and Hajj Makka, published in 1938 and 1929. Analysis of the contents of the paper was carried out using the content analysis method. Analysis of the content of the paper is categorized into the major themes of Islamic teachings, namely akidah, sharia, and akhlak. Using these criteria, we will find out the early 20th century Islamic discourse trends. This paper finds scholars in South Sulawesi with a strong background in literacy tradition. The writings of Haji Ahmad Bone and Haji Makka show the end of that long history. Based on the three Islamic themes established, the theme of sharia dominates Islamic discourse in that era. This writing contributes to uncover legacy of scholars' writings up to the beginning of the 20th century. The task of the present and future scholars is to preserve the literacy tradition.